1981
DOI: 10.1093/schbul/7.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Affective Memory and Schizophrenic Anhedonia

Abstract: Two experiments attempted to isolate and measure schizophrenic anhedonia as it is reflected in the mnemonic processing of affectively laden stimuli. In the first experiment, subjects were required to sort a list of words repeatedly, each in terms of pleasantness, until a consistent sorting was achieved. Then, they were unexpectedly asked to recall the list. Schizophrenics' total recall was comparable to that of normals; but while normals recalled significantly more pleasant than unpleasant words (a Pollyanna t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 45 publications
1
23
1
2
Order By: Relevance
“…In contrast, other forms of memory, such as motor and cognitive procedural learning (which are not dependent upon hippocampal mechanisms), appear relatively preserved in schizophrenia (Clare et al, 1993;Goldberg et al, 1993;Schmand et al, 1992). Emotional memory is likewise reported to be intact in schizophrenia, although patients show a bias for recalling more negative-affect items, while controls subjects show a bias for recalling more positive-affect items (Koh et al, 1981), again consistent with preserved or overactive amygdaloid activity in this disorder. Attentional and executive dysfunction, related to frontal pathology, may also contribute to poor episodic memory performance in schizophrenia (Maher et al, 1995;McClain, 1983), and will be considered shortly.…”
Section: Schizophreniamentioning
confidence: 76%
“…In contrast, other forms of memory, such as motor and cognitive procedural learning (which are not dependent upon hippocampal mechanisms), appear relatively preserved in schizophrenia (Clare et al, 1993;Goldberg et al, 1993;Schmand et al, 1992). Emotional memory is likewise reported to be intact in schizophrenia, although patients show a bias for recalling more negative-affect items, while controls subjects show a bias for recalling more positive-affect items (Koh et al, 1981), again consistent with preserved or overactive amygdaloid activity in this disorder. Attentional and executive dysfunction, related to frontal pathology, may also contribute to poor episodic memory performance in schizophrenia (Maher et al, 1995;McClain, 1983), and will be considered shortly.…”
Section: Schizophreniamentioning
confidence: 76%
“…Anhedonic patients have shown selective biases in recalling negative words over positive and neutral words in several studies (Calev & 580 COHEN ET AL. Edelist, 1993;Koh, Grinker, Marusarz, & Forman, 1981) suggesting that subjects' pleasurable experiences may have been recalled with an overly negativistic tone. Similarly, recent work by Herbener and colleagues (Herbener, Rosen, Khine, & Sweeney, 2007) indicated that patients as a group show impairment in encoding positive, but not negative, stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…tend to retain the negative better than the positive. Koh et al [17] hy pothesized that schizophrenics' anhedonia will lead to belter recall of negative than pos itive affect materials. They indeed found better immediate recall for negative verbal ma terials in schizophrenics, and a 'Pollyanna tendency', that is.…”
mentioning
confidence: 99%